Lessons in play an introduction to combinatorial game theory - Albert, Michael Henry; Nowakowski, Richard J. 1952-; Wolfe, David 1964- (CRC Press, Taylor & Francis Group, 2019)
Combinatorial games -- Basic techniques -- Outcome classes -- Motivational interlude -- The Algebra of games -- Values of games -- Structure -- Impartial games -- Hot games -- All-small games -- Omega
Keywords: Kombinatorisches Spiel; Game theory / Textbooks; Combinatorial analysis / Textbooks